Kolaborasi Pentahelix dalam Smart Tourism Destination Kota Semarang: Studi Kasus Pada Aplikasi Lunpia - Rino Ardhian Nugroho; Septiani Maya Lestari (Kolaborasi : Jurnal Administrasi Publik, 2023)
The development of tourism will provide many benefits for the community both economically, socially, and culturally. The integration of technology in the tourism sector is an innovation that supports sustainable tourism. The collaboration is a strategic step in tourism development. The tourism sector in Indonesia began to be developed using a collaborative approach in 2016 when the Ministry of Tourism release GBCAM synergy (governance, business, community, academy, and media) also known as the Pentahelix approach. These five elements are currently used as a model of sustainable tourism development. In the digital era, various technologies are applied to maximize the potential of tourist destinations to become smart tourism destinations. Semarang is one city apply smart tourism with the help of technology. This city develops a mobile application namely “Lunpia” to provide information about tourist destinations. This study aims to analyze the Pentahelix collaboration among tourism industry stakeholders regarding the development of the application. This study maps the role of each stakeholder in application development to support tourists in the post-pandemic situation. A qualitative approach was used in this study to get a deeper understanding of the study. The result indicated that the collaboration between stakeholders is not fully attained. The further result is discussed in the full article.